Advection Not Dispersion and Transient Storage Controls Streambed Nutrient and Greenhouse Gas Concentrations - Comer-Warner, Sophie A.; Blaen, Phillip J.; Brekenfeld, Nicolai; Gooddy, Daren C.; Lovell, Christopher; Khamis, Kieran; Bryden, Alexandra; Krause, Stefan (Frontiers in Water, 2021)
Streams and rivers are globally important in the carbon and nitrogen cycles due to high carbon and nitrogen turnover rates and contribute disproportionately to global greenhouse gas emissions relative to their areal coverage. The hyporheic zone may be a hotspot of biogeochemical reactivity within fluvial ecosystems resulting in high rates of nutrient attenuation and associated greenhouse gas production. Controls on streambed nutrient cycling and particularly greenhouse gas production remain insufficiently understood. In this study, porewater concentrations of nutrients (NH4+, NO3-, NO2-) and greenhouse gases (CO2, CH4, N2O) were measured alongside surface water breakthrough curves of conservative (uranine) and reactive tracers (resazurin (raz)-resorufin (rru)) to provide insights into often assumed correlations between in-stream advective transport and transient storage metrics, and streambed biogeochemistry. Streambed biogeochemical concentrations were significantly correlated with advective transport time but not with dispersion and transient storage. The effect of advective transport time varied between chemical species, with NH4+, CO2 and CH4 exhibiting positive correlations and NO3-, NO2- and N2O displaying negative correlations with advective transport time and vice versa for long-term storage. These findings increase knowledge of the relationship between hydrological drivers and streambed chemistry, potentially highlighting areas of the streambed expected to have elevated nutrients and GHGs. This improved understanding may allow chemical species to be effectively targeted by morphological restoration, which will aid in effective pollution and climate remediation.